Bi2O3-Layered Double Hydroxide Nanocomposites and Their Adsorption and Photocatalytic Properties - Kumari, Pooja (My University, 2023)
The present study in this thesis focus on the bismuth trioxide (Bi2O3) based nanoparticles and their nanocomposites with metal loaded ions or layered double hydroxides to know its applications in real life. Due to simpler synthesis and low cost of these nanoparticles and high efficiency these particles are modified with several other metals or LDHs to know its adsorption and photo catalytic performance. This complete thesis is divided into five chapters which are given below: Chapter 1 This chapter signifies the modification of Layered double hydroxide and Bi2O3 by varying their molar/mass ratio in order to enhance its adsorption as well as photo catalytic properties. The importance of variation in the molar/mass ratio of Bi2O3 shifts the absorption spectra in visible region and their impact on surface and electrokinetic properties. Further, as LDH and metal ion loading on Bi2O3 surface improve surface area , zeta potential properties, hydrodynamic size and heterojunction behaviour of Bi2O3 has been discussed. In this respect, research gaps have been mentioned and various methodologies adopted to complete the objectives that have been presented. Chapter 2 This chapter describes the introduction about bare Bi2O3 nanoparticles, metal ion loaded (Ni and Cu) Bi2O3 nanoparticles and their application in Naproxen and Fuschian Blue degradation under visible light irradiation. Introduction, literature review, research gap, objectives, and characterization techniques are discussed in this chapter. Chapter 3 This Chapter signifies efficient removal of eco-toxic pollutant diclophenac sodium (DCF) from wastewater. However, low adsorption capacity, high cost of conventional adsorbents limits their utility. In this context, Bi2O3 loaded Zn-Al layer double hydroxide (LDH) heterostructures (Zn-Al LDH. x Bi2O3, x= 0 to 3) have been investigated as a potential adsorbent for DCF removal .The XRD patterns confirm formation of both LDH and α-Bi2O3 phases. The flower-like morphology is evident by SEM, XPS and EDS confirm Bi2O3-LDH composite. Higher Bi2O3 loading leads to increase in the hydrodynamic sizes of the composite structure. The BET surface area and zeta potential also varies significantly with extent of loading. DCF adsorption of these composites obey the Langmuir adsorption isotherm model suggesting monolayer adsorption process whereas the intra-particle diffusion model indicates that the adsorption of DCF primarily occurs on the exterior surface. The heterostructure with x=1 exhibited ~10 times higher adsorption capacity compared to bare LDH owing to its highest surface area and positive zeta potential. Chapter 4 This chapter describe the non-steroidal drug diclofenac sodium (DCF) has emerged as hazardous pollutant due to its eco-toxic nature and its efficient elimination from wastewater is emerging as crucial problem. But, low activity, high cost and instability of the conventional photocatalysts restrain their use. In this study, different anion impreganted Cu-Al layered double hydroxides (LDH) and Bi2O3 derived hetero-composites have been examined as plausible photocatalysts for degradation of DCF under visible light radiation. The BET sorption isotherms indicate that the anion loaded composites are having larger specific surface area than the pristine one. Also, upon anion impregnation the zeta potential values shift towards more negative values confirming absorption of anions. They show significantly higher (65% for carbonate and 83% for sulphate) photcatalytic activity compare to the parent hybrid (53%). Here, the anions act as efficient electron scavengers to suppress the electron-hole pair recombination. The individual photocatalytic reactions follow pseudo-first order kinetics. Due to low cost, simpler preparation, enhanced activity and recyclability the anion loaded derivatives can emerge as excellent catalysts. Chapter 5 This chapter signifies the Ni-Al LDH–Bi2O3 (1:1) and Ni-Al LDH–Bi2O3 (1:2) LDHs have been prepared for the removal of multi-component system. These nano-catalysts were prepared by simple co-precipitation method and characterized by XRD, FESEM, EDS, Mapping, XPS, zeta, DLS and HRTEM etc. The XRD spectra confirm the presence of Bi2O3 in the NiAl LDH. Sphere like morphology is evident by HRTEM analysis. XPS studies confirm that nickel is present in 2+ oxidation state. EDS spectra confirm the presence of Ni, Al, Bi and O elements in the sample. Particle size increases on Bi2O3 loading has been confirmed by HRTEM and hydrodynamic size. Multi-component (NPX+MB) system and bare ones follow freundlich adsorption isotherms. Moreover, NPX follows pseudo-second order kinetics and MB follow pseudo-first order kinetics. Larger adsorption capacity and cost effectiveness and high efficiency, these hetero-materials could act as good adsorbents for dye and pharmaceuticals from waste water.
Keywords: Photocatalysis; Bi2O3; Layer double hydroxide; Adsorption